2019
DOI: 10.3390/nu11123009
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Decisions on Portion Size and Portion Control Strategies for Snacks in Preschool Children

Abstract: Caregivers are responsible for the type and amount of food young children are served. However, it remains unclear what considerations caregivers make when serving snacks to children. The aim of the study was to explore mothers’ decisions and portion control strategies during snack preparation in the home environment. Forty mothers of children aged 24–48 months participated in the study. Mothers prepared five snack foods for themselves and their child whilst verbalizing their actions and thoughts. Mothers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Mothers may misjudge portion sizes for children, which could be influenced by perceptual error, particularly when faced with large portions ( Hetherington et al, 2018 ). The present study provides further evidence illustrating that nutrition education, especially appropriate aids, guidance and serving size adjusted for child age and stage is needed at the point of serving, which is necessary given the potential for parental perceptual error ( Almiron-Roig et al, 2013 ; Reale et al, 2019a , b ). Furthermore, this investigation noted that mothers were enthusiastic about learning portion control from their participation in the research.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Mothers may misjudge portion sizes for children, which could be influenced by perceptual error, particularly when faced with large portions ( Hetherington et al, 2018 ). The present study provides further evidence illustrating that nutrition education, especially appropriate aids, guidance and serving size adjusted for child age and stage is needed at the point of serving, which is necessary given the potential for parental perceptual error ( Almiron-Roig et al, 2013 ; Reale et al, 2019a , b ). Furthermore, this investigation noted that mothers were enthusiastic about learning portion control from their participation in the research.…”
Section: Discussionmentioning
confidence: 69%
“…Mothers recognised large portions and realised that this might increase intake, but they may have underestimated the size of this difference, an observation that has been reported before ( Reale et al, 2019a , b ). When subdividing from large portions of food items, decisions were made by sight without using a portion aid in the observational studies.…”
Section: Resultsmentioning
confidence: 79%
“…Different assessment tasks have been used to investigate the portion size norm, including self-selected portion size tasks based on provided serving size options (12)(13)(14), normality judgement tasks using computer-based images (15), and an estimation of the number of portions contained in a package or container (16). Previous literature has shown that a range of portion sizes could be considered normal within a population, and multiple cognitive, social, and contextual factors may in uence the decision-making process and accuracy of estimations (2,3,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients. 2019;11(12):2845. PAL: estimated using the physical activity factor; classi ed into ve categories as sedentary, lightly active, moderately active, very active and extra/vigorously active(25, 26).Cooking con dence: measured using a validated 5-point Likert scale (can cook a nutritious meal; can cook a meal in a short amount of time; can cook spending a lot of money; can follow a recipe); classi ed as high if participants scored >16 out of 20 (very/extremely con dent), otherwise as low (28).…”
mentioning
confidence: 99%
“…[6] Previous research suggests parents of preschool children (de ned as one to ve years) are interested in following portion size recommendations but are not generally aware of any available. [7,8] Instead of following guidance, parents often report using instinct and experience to serve their children. [9] First-time parents of young children often seek information about feeding [10] and may be a particularly receptive audience to receiving and following portion size guidance.…”
Section: Introductionmentioning
confidence: 99%